2006
DOI: 10.1007/s11274-006-9185-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of gluco-oligosaccharides and alkyl-glucosides by transglycosylation activity of β-glucosidase from Sclerotinia sclerotiorum

Abstract: An extracellular b-glucosidase (b-glu x) from Sclerotinia sclerotiorum was used as catalyst for the synthesis of gluco-oligosaccharides (GOSs) and alkyl-glucosides. The purified b-glu x was not regiospecific for b(1 fi 4) linkages in either hydrolysis or transglycosylation catalysed-reactions. It efficiently synthesized GOSs from cellobiose, gentiobiose and methyl b-D-glucoside by transglycosylation. At optimal conditions, 119 mg/ml of GOSs (~33%) were formed over 9 h from cellobiose as substrate. Alkylglucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…This result is consistent with the reported enzymes from Stachybotrys microbispora and zygomycete R. miehei [18,21]. Krisch and other groups showed that after 35% (350 mg/ml) cellobiose was mixed with b-glucosidases for 72 h, there was 86 mg/ml cellotriose generated [18,21,22]. Cellobiose may serve as the glucosyl donor in the transglucosylation by b-glucosidase.…”
Section: Transglucosylationsupporting
confidence: 91%
“…This result is consistent with the reported enzymes from Stachybotrys microbispora and zygomycete R. miehei [18,21]. Krisch and other groups showed that after 35% (350 mg/ml) cellobiose was mixed with b-glucosidases for 72 h, there was 86 mg/ml cellotriose generated [18,21,22]. Cellobiose may serve as the glucosyl donor in the transglucosylation by b-glucosidase.…”
Section: Transglucosylationsupporting
confidence: 91%
“…Filamentous fungi S. sclerotiorum strain used in this study was isolated from sunflower Helianthus annuus and kindly provided by Professor Hajlaoui Mohamed Rabeh (Laboratory of Plant Protection, National Institute of the Agronomic Research of Tunisia, Tunis). The strain has been deposited in the VKM collection under the number VKM F‐879.…”
Section: Methodsmentioning
confidence: 99%
“…A yield of over 90% has been reported for methyl-β-D-fucoside using the Paenibacillus enzyme [59].The yields (Table 2) for higher chain alkyl glucosides range from 1.9% (decyl glucoside) to 36% (for butyl glucoside) in the reverse hydrolysis approach [19,21,54,55]. In the transglycosylation route (Table 3), the reported yield ranges from 4-97% [5,16,17,19,20,24,[26][27][28][29]53,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. As observed in Tables 2 and 3, majority of these synthesis reactions have been carried out using purified enzymes.…”
Section: Advantages Of β-Glycosidase Driven Synthesismentioning
confidence: 99%